Developing a more bicultural psychology : academic discourses of resistance : a thesis submitted in partial fulfulment of the requirements for the degree of Master of Arts, Massey University - Waldegrave, Tony (Massey University, 1996)
Psychologists through-out the world, have found themselves under increasing pressure to reflect upon the suitability of the psychological theory they present, for the contexts in which they operate (Sue, 1993). In New Zealand this concern is manifested in a call for the development of a more bicultural psychology. This recognises the poor performance of Maori in academic and professional psychology, and draws attention to issues of bicultural partnership prescribed by a document of constitutional significance in New Zealand, the Treaty of Waitangi. Despite disciplinary intention to develop more biculturally, successive surveys have found that the movement toward this goal has been slow. Such findings prompted the present study, which considers whether conditions are conducive to the provision of the recommended changes. Issues of bicultural development were discussed with ten non-Maori psychology lecturers, from two New Zealand universities. A discourse based analysis of the transcripts was undertaken. This drew attention to procedures by which lecturers made sense of Maori concerns and the discipline's responses. The participants discourses were found to resist Maori concerns for bicultural development. This was achieved by undermining the validity of concerns, by claiming Maori were unfairly treated, by presenting current performance in a positive light, or by drawing attention to difficulties of being able to respond productively. These discourses used Pakeha values of legitimacy as commonsense rationale to resist changes. This process of legitimisation was determined to provide a barrier to the bicultural development of the discipline because it asserted monocultural control of a bicultural process. Attempts to account for Maori psychological needs and to capture the 'spirit and intent' of the Treaty of Waitangi would therefore work to accommodate Maori perspectives which could be legitimised by Pakeha values. On this basis it is argued that bicultural development is dependant upon the establishment of a dynamic of mutual accountability, on space being made for Maori values and the ability of Pakeha to assume an active role to facilitate ideological and systemic reflexivity, among students who may not otherwise have had this opportunity.
Keywords: Psychology; Psychologists; Ethnopsychology; New Zealand; Higher educaiton; Attitudes; Biculturalism